SWASTANISASI PERKEBUNAN TEH DI BOGOR 1905—1942 - Nurbaity Nurbaity; Saring Saring (Sosio e-Kons, 2015)
Indonesia known as Nusantara by East-Indies had greatest natural sources. The search of spices in East-Indies by the westners of Europe had been done since the emerge of compass and shipping technology. The potential of Nusantara’s natural resources commodities sold out in world’s market forced west countries to compete and gained much more benefits. Those benefits too-and yet become the motivation of the west to occupy the land. The more greater power to the west then later be implemented through several rules and obligations including in economic called cultuurstelsel. The cultuurstelsel then later be changed within the involvement of private sector in it and given their investment. One of the investment in occupied land is the acquisition of tea plantation in Cipanas Bogor. This acquisition of tea plantation become private sector had marked his own periode in the history of plantation in Indonesia. Keywords: Cultuurstelsel, export commodities, private plantation, Bogor